Procedural skills training for Canadian medical students participating in international electives - Margolick, Joseph; Kanters, David; Cameron, Brian (Canadian Medical Education Journal, 2015)
Background: International medical electives (IMEs) are unique learning opportunities; however, trainees can risk patient safety. Returning medical students often express concern about doing procedures beyond their level of training. The Canadian Federation of Medical Students has developed guidelines for pre-departure training (PDT), which do not address procedural skills. The purpose of this research is to determine which procedural skills to include in future PDT. Methods: Twenty-six medical students who returned from IMEs completed surveys to assess PDT. Using a Likert scale, we compared procedures performed by students before departing on IME to those performed while abroad. We used a similar scale to assess which procedures students feel ought to be included in future PDT. Results: There was no significant increase in number of procedures performed while on IME. Skills deemed most important to include in future PDT were intravenous line insertion, suturing of lacerations, surgical assisting and post-operative wound care. Conclusions: Pre-departure training is new and lacks instruction in procedural skills. Over half the students rated several procedural skills such as IV line insertion, suturing, assisting in surgery, post operative wound management and foley catheterization as important assets for future PDT.